2009
DOI: 10.1111/j.1439-0388.2008.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic description of a divergent selection experiment in Angora rabbits with overlapping generations

Abstract: The chief aims of this paper were the following: (i) to describe the demography and genetic structure in two divergent selected lines for total fleece weight (TFW) of French Angora rabbits with overlapping generations; (ii) to describe the effects of inbreeding during an experiment of divergent selection. A study of longevity with the survival kit showed that there was no significant difference in the risk of death or culling between the low line (LL) and high line (HL). A significant effect of inbreeding (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…When compared with other commercial breeds of rabbits, the effective size in the present study is found to be much smaller, which can be attributed to the higher rate of inbreeding in the population. The effective size reported in 2 different lines of Angora rabbits ranged from 29 to 47 (Rafat et al, 2009) and in Pannon White rabbits from 37.19 to 91.08 (Nagy et al, 2010). However, this effective size is higher than the value (9.6) reported by Martín de la Rosa et al (2016) in Ibicenco rabbit population.…”
Section: Effective Population Sizementioning
confidence: 61%
See 1 more Smart Citation
“…When compared with other commercial breeds of rabbits, the effective size in the present study is found to be much smaller, which can be attributed to the higher rate of inbreeding in the population. The effective size reported in 2 different lines of Angora rabbits ranged from 29 to 47 (Rafat et al, 2009) and in Pannon White rabbits from 37.19 to 91.08 (Nagy et al, 2010). However, this effective size is higher than the value (9.6) reported by Martín de la Rosa et al (2016) in Ibicenco rabbit population.…”
Section: Effective Population Sizementioning
confidence: 61%
“…The mean generation interval presently studied for the whole population of New Zealand White rabbit was 1.49 yr (543 d), which is comparable with earlier reports on rabbit populations. Rafat et al (2009) reported the average generation interval of 1.54 yr (562 d) and 1.64 yr (601 d) for 2 different lines (LL and HL) of Angora rabbits in France. Nagy et al (2010) studied the generation interval on Pannon White rabbits in Hungary and reported the overall mean as 1.211 yr for the whole population.…”
Section: Generation Intervalmentioning
confidence: 99%
“…Moreover, most natural and artificial populations have overlapping generations. In addition, breeding organisations are interested in utilizing overlapping generations (Rafel et al 1990;Rafat et al, 2009). The renewal of the next generation after selection was composed each year of 36 females and 5 males alive at the second harvest in each line.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…For Angora rabbits under the same environmental conditions, gender, body site, and the month of age are closely related to wool bre production [3]. Genetic factors that in uence wool bre production are bre diameter, length, neness, and the bre density [3][4][5][6][7]. The mean hair follicle density depends on the skin area.…”
Section: Introductionmentioning
confidence: 99%